Análisis de escurrimientos máximos en Los Arroyos El Cangrejo y El Coajinque: huracán Lidia, Autlán Jalisco, México: Analysis of Maximum Runoff in the El Cancrejo andCoajinque Streams: Hurricane Lidia, Autlán Jalisco, Mexico - Ceron Galindo, Christian Yael (2025)
Surface runoff originates from factors such as different rainfall intensities, relief, physical environment of the soil and vegetation cover, in which a certain control is exercised. The data analysis was through the characterization of tributary basins, with a slope of 38%, time of concentration of 109 minutes for the El Cangrejo basin and 133 for El Coajinque basin, the predominant soil in both basins is of the Regosol type; the meteorological stations located within the basins were considered, which register a maximum rainfall intensity for return periods of 2 to 100 years of 22. 6 to 53.4 mm hr-1 for the Autlán station and 42.5 to 100.4 mm hr-1 for El Jalocote. The maximum flood was estimated at 2 hours for El Cangrejo and 2.45 for El Coajinque, a situation that favors the risk of flooding in the lower part of the basins and valley zone. The maximum footprints were evaluated for a similar flow, it was greater for El Cangrejo with 936.3 m3 s-1. The trend suggests alternating periods of maximum daily rainfall outside the range of the average value of 4 to 18 years with the presence of events that could impact lower areas of the tributary basins.